P08-S Combined electromagnetic source imaging in presurgical evaluation. Issue 7 (July 2019) - Duez, Lene; Tankisi, Hatice; Hansen, Peter Orm; Sabers, Anne; Pinborg, Lars; Fabricius, Martin; Rásonyi, György; Rubboli, Guido; Pedersen, Birthe; Leffers, Anne-Mette; Uldall, Peter; Jespersen, Bo; et al.
Abstract : Background: To date, source imaging (SI) has been performed using epileptiform discharges (ED) detected by magnetoencephalography (MEG) or electroencephalography (EEG). A few case studies has combined MEG and EEG recordings and performed electromagnetic source imaging (cEMSI). This study tries to elucidate the role of cEMSI in presurgical evaluation. Material and methods: A MEG whole-head 306-channel Elekta Neuromag® system, and simultaneous high density EEG (70 electrodes, range 58–80) using a non-magnetic cap (EASYCAP) were recorded in 141 consecutive patients. Fifty patients were operated and had one year follow up. MEG-EEG was inspected for EDs. Signals were analyzed using CURRY 7 Neuroimaging Suite. For each cluster, using the visually detected EDs as templates, automated algorithms scanned the recordings, and detected EDs were visually checked. To improve the signal-to-noise ratio, EDs with similar topography were averaged. Two different inverse solutions were applied: equivalent current dipole (ECD) and a distributed source model (DSM): sLORETA. We performed electric SI, magnetic SI, and cEMSI. All analyses were performed using individual head models from the patients' MRIs. We calculated the odds ratio (OR) of becoming seizure-free when operation was concordant vs discordant with the localization of the SI. Results: Combining both EEG and MEG signals (cEMSI) gave an OR of 5.8 for ECD and 19.2 for DSM. OR of cEMSI using DSM was significantly higher than both ESI ( p = 0.02) and MSI ( p = 0.03). Conclusion: Combined EMSI achieved significantly higher odds ratio for becoming seizure-free compared to electric SI and magnetic SI.